Salud mental y tipos de estrategias de comunicación de pareja en mujeres auxiliares de enfermería de un centro de salud (2022)
Due to the different sociocultural changes, the incorporation of women into the labor market is becoming more frequent, with a considerable participation of auxiliary nursing professionals, considering previous research related to mental health, there is evidence of a high vulnerability of psychological alterations in this profession, consequently the professional may be exposed to physical, cognitive, and emotional changes, which may affect the type of communication strategy with the partner. Therefore, a descriptive quantitative study was carried out in which the variables of mental health and the types of communication strategies in couples were analyzed in a sample of 75 female nursing assistants of a health center, the instruments used were the mental health inventory (SWS) and the questionnaire of assertion in couples (ASPA), and information was also collected through the application of a sociodemographic card.